Eksplorasi Budaya Jepang melalui Pendidikan di SMAS Pondok Pesantren Modern Nurul Ikhlas X Koto - Idea Alvira; Fauziah Sri Andria Hafid; Well Victory; Meria Eliza (Pakis Journal Institute, 2026)
Cross-cultural understanding and international insight have become crucial to study in the era of globalization, both through formal and non-formal educations. Such learning serves as a strategic endeavor to equip learners to handle contemporary challenges, both as individuals and as social beings. In this regard, this community service aims to introduce and provide an understanding of how education in Japan is implemented, particularly regarding character education. This program was conducted at SMAS Pondok Pesantren Modern Nurul Ikhlas, with participants being grade 5 students (equivalent to grade XI). By introducing the character education practiced in Japan, it is hoped that students' characters will be strengthened and they will gain an understanding of global cultural diversity. The method used in this program was an interactive lecture between the students and the presenters. The activity was conducted in an orderly manner, and the students showed great enthusiasm throughout the session. The materials provided consisted of the Bushido principles—which are part of the history of character education in Japan—as well as character education in schools, at home, in society, and in the work environment. The activity concluded with a Q&A session where rewards were given to students who could answer the presenters' questions. Through this program, it is hoped that students will adopt positive Japanese cultural values to enhance their soft skills.